2021
DOI: 10.18006/2021.9(1).44.50
|View full text |Cite
|
Sign up to set email alerts
|

IN VITRO RESPONSE BY Terminalia arjuna GENOTYPES DURING MICROPROPAGATION

Abstract: Terminalia arjuna is an important tree of the medicinal and sericulture industry, commonly known as Arjun. It’s bark is rich in secondary metabolites makes this plant highly valuable in medicine industry to treat cardiovascular disease. Overexploitation due to high demand in medicine, low seed germination, limitations of the conventional method of propagation push this plant towards being endangered. To conserve germplasm of such tree species and meet the requirement in medicinal industry, some non-conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…without any PGR (Table 1). These results are in agreement with earlier studies where BA was found to be beneficial for in vitro shoot multiplication of various plant species including E. alba (Bhaskaran and Jayabalan 2005;Choudhary et al 2021;Iiyama and Cardoso 2021).…”
supporting
confidence: 93%
“…without any PGR (Table 1). These results are in agreement with earlier studies where BA was found to be beneficial for in vitro shoot multiplication of various plant species including E. alba (Bhaskaran and Jayabalan 2005;Choudhary et al 2021;Iiyama and Cardoso 2021).…”
supporting
confidence: 93%